Pasture or permanent crops after slash-and-burn cultivation? Land-use choice in three Amazon colonies - Fujisaka, Sam; White, D. (Springer, 1998)
Land use was examined in three settlements Pedro Peixoto in Acre and Theobroma in Rondonia, Brazil, and Pucallpa, in Peru. Research aimed at characterizing the differences in land use after initial slash-and-burn, and presenting hypotheses to assess the feasibility of improved land uses. Settlers in the Amazon practice slash-and-burn agriculture in forest lands to produce annual crops. After cropping, lands are converted to pasture, or planted with perennial crops, or fallowed in anticipation of future annual crop production. Land use after slash-and-burn cultivation in forest lands differed among the colonies examined. Whereas colonists in Pedro Peixoto converted lands to pasture for cattle production, settlers in Theobroma adopted a strategy encompassing both dual-purpose (milk and meat) cattle and perennial crop production. The more heterogeneous settlers in Pucallpa, who included small-scale cattle ranchers and riverine and forest slash-and-burn farmers, gave more importance to perennial crops. Hypotheses are suggested regarding the described land use differences, and implications for the adoption of agroforestry are discussed.